DISTRIBUTION OF DTPA EXTRACTABLE MICRONUTRIENTS IN SOILS OF SOUTHERN REGION OF TELANGANA STATE - V. PRAVEEN RAO, M. RAM PRASAD, P. RAVI, CH. CHANDRASEKHAR, V. GOVERDHAN and (The Journal of Research, PJTSAU, 2017)
Thirty nine soil samples from ten pedons of Southern region of Telangana state were studied for vertical distribution of DTPA extractable Zn, Cu, Fe and Mn and their relationship with soil properties. Soil reaction (pH), organic carbon, calcium carbonate and particle-size fractions had strongly influence on the distribution of these micronutrients of the soil. The content of micronutrients increased with the increase in organic carbon and decreased with increase in pH and CaCO3. There was a decreasing trend for the content of these micronutrients with increasing depth of the soil. As per critical limit prescribed for zinc 20 per cent of the surface soils could be rated as deficient in available zinc. Available iron, copper and manganese content of the soils were found to be adequate in the selected pedons Southern region ofÂ Telangana state.